Sensitivity Analysis of Wave Slamming Load with Respect to Wind Load for Semi-Submersible Platform Design - 霍发力 张会新 索健 杨德庆 崔锦 (Shanghai jiao tong da xue xue bao, 2015)
A design of offshore floating structure is mainly based on the extreme response analysis due to the forces experienced. The extreme response can induce the negative air gap response and potential impact to the deck bottom of floating structure. It is important to predict the slamming load in order to check the strength of local structures which withstand the wave slamming. In recent years, studies of the effects of wind load on air gap response and slamming load are ignored. When the platform suffers the extreme wave, the wind is also harsh.Moreover, the wind load can affect the motion response of the platform. The wind load cannot be simulated easily by model test in towing tank whereas it can be simulated accurately in wind tunnel test. Though the model test results are not accurate enough for air gap and slamming load evaluation due to the loss of wind effect, they can be used as a good basis for tuning the radiation damping and viscous drag in numerical simulation. This paper aims at presenting the sensitivity analysis results of wave slamming load with respect to the wind load for the design of semi-submersible platform. As an example of semi-submersible drilling platform design, the wind tunnel test has been carried out, and the sea-keeping model test is also performed in towing tank, while the wind load effect is ignored. According to the model test results, a numerical model is tuned and validated by ANSYS AQWA. Sensitivity analysis studies of the relative velocity between water particle and platform surface and the wave slamming load with respect to the wind load are performed in time domain by the tuned numerical model.Five simulation cases about the presented platform are simulated based on the results of wind tunnel tests and sea-keeping tests. The sensitivity analysis results are valuable for the floating platform design.